Differences in judo attack systems between weight categories - Kashiwagura, D. B.; Courel-Ibáñez, J.; Kashiwagura, F. B.; Agostinho, M. F.; Franchini, E. (Journal of Science in Sport and Exercise, 2023)
Purpose In judo, athletes compete based on weight categories, which are required to adapt the training process accordingly, but not enough research is present to understand their particularities. The present study aimed to verify the differences in judo attack systems performed between the seven male weight categories in world-class athletes.